The Influence of Principal's Leadership Style and Organizational Culture on Teacher Performance - Narullita, Narullita; Fitria, Happy; Mulyadi, Mulyadi (Graduate Program Magister Manajemen Pendidikan, 2022)
This study examined and analyzed the influence of principal's leadership style and organizational culture on teacher performance. In this study, the method used was the quantitative. The data were collected using questionnaire. The results showed that there is significant influence of principal's leadership style and organizational culture on teacher performance partially and simultaneously. The paper provides the insight of principal for more upgrading leadership style and organizational culture where the school would have good teacher performance.